Treatment of acute cystitis in Hungary: comparison with national guidelines and with disease-specific quality indicators. (August 2013) - Juhasz, Zoltan; Benko, Ria; Matuz, Maria; Viola, Reka; Soos, Gyongyver; Hajdu, Edit
Abstract Background: The aim of this study was to compare Hungarian antibiotic use in acute cystitis with the internationally developed disease-specific quality indicators and with the national guidelines. Methods: The aggregated national-level data on systemic antibiotic use was purchased from the National Health Fund Administration. The study period was January–June 2007. Antibiotic use in acute cystitis was evaluated by means of the defined daily dose (DDD) methodology. Quality indicators of antibiotic prescribing proposed by the European Surveillance of Antimicrobial Consumption (ESAC) team were the usage rate of recommended antibacterials and the usage rate of quinolones. Adherence to the available national guidelines was determined. Results: For acute cystitis, 1.06 DDD per 1000 inhabitant-days antibiotic use was recorded. The ESAC recommended antibiotic use in cystitis (23.3%) was well below the recommended range (80–100%). The consumption of fluoroquinolones was 56.2%, which exceeded the recommended range (0–5%) more than 10 times. The adherence rate to the Hungarian guidelines ranged between 59.3% and 74.2%. Conclusions: As both investigated disease-specific quality indicators were well outside the acceptable ranges, some inappropriateness of antibiotic use in cystitis seems to be present. Adherence rates to the different national guidelines were also moderate, but due to the general recommendation of quinolones, values should be interpreted with caution. New transparent guidelines – issued by the Hungarian Society of Family Physicians – should be introduced in Hungary, recommending quinolones only for second-line therapy.